2018
DOI: 10.1155/2018/4564328
|View full text |Cite
|
Sign up to set email alerts
|

STAT1, IGF1, RAC1, and MDM2 Are Associated with Recurrence of Giant Cell Tumor of Bone

Abstract: Background In our previous study, mouse double minute 2 homolog (MDM2), insulin-like growth factor 1 (IGF1), signal transducer and activator of transcription 1 (STAT1), and Rac family small GTPase 1 (RAC1) were correlated with the recurrence of giant cell tumor of bone (GCT). The aim of this study is to use a large cohort study to confirm the involvement of these four genes in GCT recurrence. Methods The expression of these four genes was detected and compared between GCT patients with or without recurrence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Comparing the osteosarcoma, Ewing sarcoma, and GCT groups, the overexpression of the IGF-1 axis was more prominent in osteosarcoma and Ewing sarcoma compared to GCT which might be influenced by higher tumor grades and disease stages in these groups. It was shown that the expression level of IGF-1 in recurrent GCT was significantly higher than in non-recurrent GCT subjects (33); however, GCT cases in our study were GCT patients without recurrence. Most of the studies in the literature regarding the IGF-1 axis in bone tumor pathogenesis are focused on determining the functional mechanism of this axis.…”
Section: Discussioncontrasting
confidence: 69%
“…Comparing the osteosarcoma, Ewing sarcoma, and GCT groups, the overexpression of the IGF-1 axis was more prominent in osteosarcoma and Ewing sarcoma compared to GCT which might be influenced by higher tumor grades and disease stages in these groups. It was shown that the expression level of IGF-1 in recurrent GCT was significantly higher than in non-recurrent GCT subjects (33); however, GCT cases in our study were GCT patients without recurrence. Most of the studies in the literature regarding the IGF-1 axis in bone tumor pathogenesis are focused on determining the functional mechanism of this axis.…”
Section: Discussioncontrasting
confidence: 69%
“…Multiple genes influence the biological behaviour of prostate cancer cells by regulating MMP1 52–54 . STAT1 may activate the immune system of cancer patients 55,56 . However, abnormal low expression of STAT1 may create conditions for tumour immune escape 57 .…”
Section: Discussionmentioning
confidence: 99%
“… 52 , 53 , 54 STAT1 may activate the immune system of cancer patients. 55 , 56 However, abnormal low expression of STAT1 may create conditions for tumour immune escape. 57 At present, some studies have confirmed that some kinds of cancer cells, including melanoma, squamous cell carcinoma and gastric carcinoma, can achieve the purpose of immune escape by downregulation of STAT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the group of Chen et al [ 50 , 51 ] assessed differentially expressed genes in the recurrent GCTB through microarray and IHC, identifying four genes with a statistically significant association with GCTB recurrence: mouse double minute 2 homolog (MDM2) ( p = 0012), insulin-like growth factor 1 (IGF1) ( p = 0033), signal transducer and activator of transcription 1 (STAT1) ( p = 0026) and Rac family small GTPase 1 (RAC1) ( p = 0007), suggesting they might be used as biomarkers for GCTB recurrence.…”
Section: Gctb Cytology Histopathogenesis and New Biomarkers In Molecular Targeted Therapy Eramentioning
confidence: 98%